Identifikasi Kandungan Merkuri pada Handbody Lotion Whitening yang Dijual di Online Shop Daerah Jawa Tengah Tanpa Ijin BPOM - Risa Mega Legina; Kharismatul Khasanah (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Mercury (Hg) is illegally used in cosmetics as a skin whitener because it can inhibit the formation of melanin, but it poses health risks as it can accumulate in the body. The use of mercury-containing whitening lotions can cause serious side effects. This study aims to identify the presence of mercury in handbody lotion sold in online shops in Central Java without BPOM approval. The method used is Descriptive Qualitative with a color reaction test. The results show that out of 6 samples tested, samples A, B, C, D, and E were mercury-negative, while sample F tested positive for mercury based on two tests, namely the Rapid Test Kit and the Amalgam formation test.